Effect of Supportive Educational Intervention for Mothers of Female Adolescents with Cerebral Palsy on Their Caring Practices - Safaa F. Draz; Amal T. A. Elsharkawy (Evidence-Based Nursing Research)
Context: Cerebral palsy is a major cause of poor physical, mental, and social health and one of the biggest risk factors for underachievement in later life. Mothers are caring for children with disabilities experience several challenges. Parents of children with cerebral palsy (CP) must know about the disease and its management to improve the outcome.